Cadomian/Pan-African consolidation of the Iberian Massif assessed by its detrital and inherited zircon populations: is the ~610Ma age peak a persistent Cadomian magmatic inheritance or the key to unravel its Pan-African basement? - Martim Chichorro; Ana Rita Solá; Telmo M. Bento dos Santos; João Lains Amaral; Lourenço Crispim (Geologica Acta, 2022)
This work assessed the age distribution of Cadomian/Pan-African orogenic events (550-590 and 605-790Ma, respectively) in several zones of Iberian Massif by means of detrital and inherited zircon analysis compilation. Detrital zircon age spectra show that throughout the late Neoproterozoic-to-Early Ordovician era (~120Ma sedimentary record), the main systematic peak occurs at ~610Ma, followed by peaks at typical Cadomian ages (~590-550Ma). Inherited zircons incorporated in Cambrian-to-Lower Ordovician igneous rocks show typical Cadomian ages (~590-550Ma) but, once again, a remarkably consistent Pan-African ~610Ma peak occurs. In accordance with compiled zircon data and taking into account the evidence of North African peri-cratonic inliers, Ediacaran (~610Ma) zircons incorporated in Paleozoic magmas provide indirect evidence of Pan-African magmatism, suggesting that these magmas and synorogenic sediments are likely to constitute the cryptic stratigraphic infrastructure of most of the Iberian Massif. The main source of ~610Ma inherited zircons may be the lateral chrono-equivalents of the Saghro and Bou Salda-M`Gouna Groups (Anti-Atlas, Morocco) and/or coeval igneous rocks from West African Craton or Trans-Sahara Belt, emplaced at a stratigraphic level below the late Ediacaran sediments of the Ossa Morena Zone and the Central Iberian Zone. Assuming that the Iberian crust is a fragment of the Pan-African orogen, a relative paleoposition situated between the West African Craton and the Trans-Saharan Belt during the Late Neoproterozoic is proposed. The closed-system behaviour of Stenian-Tonian detrital zircon ages in the Trans-Sahara Belt suggests that this mega-cordillera acted as a barrier, in paleogeographic terms, to separating the Sahara Metacraton from Iberia. In Iberia, the opening of the system to Stenian-Tonian detrital zircon during the Ordovician indicates that, at that time, the Trans-Saharan Belt had already become a vast peneplain, which favoured a large drainage system with a long-distance transport mechanism that fed the passive continental margins.